Métricas m-quasi-Einstein em variedades compactas - Diógenes, Rafael Jorge Pontes (2012)
Our objective in this work is to present a generalization of quasi-Einstein metrics for vector field is not necessarily smooth gradient also present some integral formulas for compact quasi-Einstein metrics defined in a compact and as application set out three important results, one being characterized such classes for a compact manifolds of dimension two.